O52: THE IMPACT OF STUDENT BACKGROUND ON PERFORMANCE AND STRESS DURING SURGICAL SIMULATION. (27th April 2021) - Soualhi, A; Amin, MSA; Aydin, A; Khan, MS; Dasgupta, P; Makanjuola, J; Ahmed, K
Abstract: Introduction: Early exposure of medical students to surgical skills has been associated with an increased interest in pursuing a career in surgery. This study aimed to investigate the impact of student background on basic laparoscopic skills acquisition and perceived stress to workload during simulation. Method: Students were recruited to a course modelled on the European Basic Laparoscopic Urological Skills (E-BLUS) programme. Students filled out a pre-course demographic survey, and a post-course survey that evaluated perceived stress to workload (SURG-TLX). Pre- and post-course confidence in laparoscopic skills, performance in the course, as well as SURG-TLX parameters were statistically compared for all demographic factors. Result: Twenty-three participants completed the course, fifteen (65%) of which were female. Ten students were junior (first and second year), and thirteen were senior (third year and above). Hobbies were grouped into either requiring hand-eye coordination (n=9), manual dexterity (n=9), or no relevance to surgery (n=5). No significant differences were found in demographic factors for course performance or pre- and post-course confidence. No significant differences were found between male and female students, and between different hobby groups, in all SURG-TLX parameters. Senior students reported a significantly higher Physical Demand of the SURG-TLX compared to juniors (p=0.042). No differences were found in other parameters. Conclusion: Our study showed no correlation between student background (notably sex and stage of medical school) and basic laparoscopic skills acquisition or stress during simulation. We therefore suggest that medical students are provided with more exposure to acquire basic laparoscopic skills regardless of their background. Take-home message: Medical student background is not a discriminator in surgical simulation performance and stress. All medical students, regardless of their sex or stage of medical school, should be given the opportunity to practice laparoscopic skills.